What Happens When You Play the Game? The Impact of Political Skills on Organizational Based Self Esteem and the Moderating Effect of Gender - Kohli, Anchal Kaur (2022)
Abstract The aim of the present study is to examine the impact political skills can have on an individual’s organizational based self-esteem. Furthermore, the study considers the moderating impact gender can have on this relationship. All four dimensions of political skills (networking ability, social astuteness, interpersonal influence and apparent sincerity) were examined in this present research. Previous literature has pointed to political skills being an antecedent to several positive job outcomes and attitudes such as self-efficacy, stress tolerance and organizational commitment (Kimura 2015). However, while introduced, the relationship between political skills and self-esteem is still underdeveloped. Organizational based self- esteem refers to the an individuals feelings of self-worth as a member of and organization and differs from general self-esteem (Peirce, Gardner, Cummings and Dunham 2004). Additionally, it is well known that women’s experience in the firm differ from that of men, such that they are likely to be faced with more negative situations which can impact feeling of self-worth (Buchanan and Badham 2008). As such, this may have a moderating affect on the relationship between political skills and organizational based self-esteem. The finding of this study found a moderate positive correlation between political and Organizational based self-esteem but could not establish any moderating effect of gender. Keywords: Political Skills, Organizational Based Self Esteem, Gender, Self-Evaluations